2012
DOI: 10.1111/j.1365-2435.2012.01996.x
|View full text |Cite
|
Sign up to set email alerts
|

Sociality level correlates with dispersal ability in spiders

Abstract: Summary1. The evolution of sociality alters the genetic structure of populations, often leading to an increase in the level of inbreeding and a concomitant decrease in the ratio between the benefits and costs of dispersal. 2. The association between an absence of dispersal and sociality in spiders has so far been established indirectly from the age distribution of colonies, their genetic structure and their sex ratio. Using a functional and mechanistic approach, we investigated the dispersal tendencies and abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 62 publications
2
15
0
Order By: Relevance
“…A previous study found a negative association between the degree of cell cooperation and short-distance dispersal, as dispersal is likely to disrupt group structure (Schtickzelle et al 2009). However, specialized morphs capable of long-distance dispersal are more frequent within cooperative genotypes of T. thermophila (Schtickzelle et al 2009), with similar findings also known for spiders (Corcobado et al 2012). Therefore, a likely explanation for an overall negative density-dependent pattern of dispersal in our experiments might stem from the density-related effects of cooperation previously detected in T. thermophila.…”
Section: Propensity Plasticitysupporting
confidence: 87%
“…A previous study found a negative association between the degree of cell cooperation and short-distance dispersal, as dispersal is likely to disrupt group structure (Schtickzelle et al 2009). However, specialized morphs capable of long-distance dispersal are more frequent within cooperative genotypes of T. thermophila (Schtickzelle et al 2009), with similar findings also known for spiders (Corcobado et al 2012). Therefore, a likely explanation for an overall negative density-dependent pattern of dispersal in our experiments might stem from the density-related effects of cooperation previously detected in T. thermophila.…”
Section: Propensity Plasticitysupporting
confidence: 87%
“…If it is due to a common dispersal distance, then social and subsocial species would appear to correspond to two discrete behavioural syndromes, whereby a shift from one state to the other requires a qualitative change to the system itself, consistent with a discrete categorization of ‘solitary’, ‘subsocial’ and ‘social’. The latter suggestion is only partially consistent with the findings of Corcobado et al (), who show that there is a significant difference in dispersal tendencies and abilities of social and subsocial spiders, but enough of a gradation within the two categories for the change to be more or less continuous rather than abrupt.…”
Section: Discussionsupporting
confidence: 74%
“…Other traits that may also correlate with level of sociality in spiders, but are not considered here, include dispersal propensity (Corcobado et al. ), degree of inbreeding (Avilés ), sexual size dimorphism, the extent to which males participate in communal activities and the degree of allomaternal care (Samuk et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the social and subsocial spiders, the genus Anelosimus remains one of the better studied. The less social species within this genus are more likely to disperse than the more social species (Corcobado et al., ). There remain fundamental questions unresolved in the Anelosimus genus with respect to the immediate details of dispersal.…”
Section: Introductionmentioning
confidence: 99%
“…Two major shifts in dispersal patterns are thought to be key factors in the evolution of sociality in spiders: (i) An extended period of maternal care, which deters spiderlings from early dispersal as juveniles from the maternal web (Yip & Rayor, 2014), and (ii) The suppression of the dispersal phase of subsocial spiders allowing for overlapping of generations and communal breeding (Agnarsson, 2012;Corcobado et al, 2012;Pruitt & Avilés, 2018;Whitehouse & Lubin, 2005;Yip & Rayor, 2014). The propensity of group living spiders to disperse and the timing of dispersal events are key features of the gradient of sociality (Corcobado et al, 2012). In cooperative spiders, most individuals forego dispersal to breed communally.…”
mentioning
confidence: 99%